2004
DOI: 10.1179/027249304225013448
|View full text |Cite
|
Sign up to set email alerts
|

Post-neonatal infant mortality in Malawi: the importance of maternal health

Abstract: In a cohort study of mothers and their infants, information was collected from women attending the antenatal services of two hospitals in a rural area of Malawi and 561 of their babies were enrolled in a follow-up study. There were 128 with a low birthweight (LBW, <2500 g), 138 with fetal anaemia (FA, cord haemoglobin <12.5 g/dl), 42 with both and 228 with a normal birthweight and no FA. Infants were seen monthly for 1 year. Risk factors for post-neonatal infant mortality (PNIM) were calculated using Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
4
23
2
2
Order By: Relevance
“…Overall, the risk on PNIM was actually lower, although not significantly so, in infants born to HIVinfected mothers with placental malaria (AHR, 0.77 [95% CI, 0.43-1.39]), and this remained so after adjustment for potential confounders, including maternal CD4 + cell counts and LBW. These results are consistent with those of another study [19] that reported a nonsignificant protective effect of placental malaria against PNIM among infants born to HIV-seropositive women (HR, 0.39 [95% CI, 0.11-1.38]). We previously reported that MTCT was significantly lower in infants born to mothers with placental malaria than in those without placental malaria [12].…”
Section: Discussionsupporting
confidence: 94%
“…Overall, the risk on PNIM was actually lower, although not significantly so, in infants born to HIVinfected mothers with placental malaria (AHR, 0.77 [95% CI, 0.43-1.39]), and this remained so after adjustment for potential confounders, including maternal CD4 + cell counts and LBW. These results are consistent with those of another study [19] that reported a nonsignificant protective effect of placental malaria against PNIM among infants born to HIV-seropositive women (HR, 0.39 [95% CI, 0.11-1.38]). We previously reported that MTCT was significantly lower in infants born to mothers with placental malaria than in those without placental malaria [12].…”
Section: Discussionsupporting
confidence: 94%
“…Hypoplasia in the deciduous dentition has been shown to occur in modern children from parts of Africa and African refugee populations, where lancing of the alveolar bone overlying the deciduous canine crown and the full or partial removal of the forming tooth is performed as traditional treatment for infant health problems (Dewhurst and Mason, 2001;Hassanali et al, 1995;Holan and Mamber, 1994;Muriithi and De Souza, 2002;Rasmussen et al, 1992;Rodd and Davidson, 2000;Welbury et al, 1993). Suckling (1986), in her experimental research with sheep, induced hypoplastic defects through physical trauma to developing permanent incisor crowns.…”
Section: Localised Hypoplasia Of the Primary Caninementioning
confidence: 95%
“…Although LHPC form postnatally, they are probably related, in part, to in utero health. This argument is based on the fact that mortality and morbidity in infants in living populations is shown to be strongly related to in utero stress (Kramer, 2003;Pawley and Bishop, 2004;Verhoeff et al, 2004).…”
Section: Localised Hypoplasia Of the Primary Caninementioning
confidence: 98%
“…Majority of pregnant women in developing countries, where rate of LBW is high, are heavily exposed to indoor air pollution, increased relative risk translates into substantial population attributable risk of 21% of LBW [4]. Low birth weight infants have 3-4 times greater risk of dying from diarrhea and acute respiratory infection as compare to normal birth weight babies [5]. For many women in the developing world however, economic, social and cultural factors make it difficult for them to obtain the necessary food and health care, which are closely interrelated and these the risk factors are low socioeconomic conditions low education status maternal age, short birth interval, maternal weight and height, multiparty and maternal medical conditions like hypertension, anemia and diabetes [6].…”
Section: Introductionmentioning
confidence: 99%